1988
DOI: 10.1111/j.1464-5491.1988.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

An Amperometric Needle‐type Glucose Sensor Tested in Rats and Man

Abstract: An amperometric glucose-measuring 25 gauge (0.5 mm diameter) needle-type sensor has been developed using a glucose oxidase and dimethyl ferrocene paste behind a semi-permeable membrane situated over a window in the needle. Electron transfer results in direct current generation. Sensors have been tested subcutaneously in the abdomen both in anaesthetized rats (40 sensors, 11 rats) and in normal, conscious man (20 sensors, 10 subjects). In rats the blood glucose was modulated by glucose and by insulin infusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…For this reason, they have been used extensively in other areas of biology and medicine, in vitro and in vivo, as auxiliary and/or reference electrodes, for the measurement of dissolved oxygen (8), pH (11), ions (12), glucose (13), and other species (14). Recently, two groups developing needle-type subcutaneous glucose sensors (15,16) proposed silver/silver chloride electrocardiogram external reference electrodes as an alternative to implanted auxiliary/reference electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, they have been used extensively in other areas of biology and medicine, in vitro and in vivo, as auxiliary and/or reference electrodes, for the measurement of dissolved oxygen (8), pH (11), ions (12), glucose (13), and other species (14). Recently, two groups developing needle-type subcutaneous glucose sensors (15,16) proposed silver/silver chloride electrocardiogram external reference electrodes as an alternative to implanted auxiliary/reference electrodes.…”
Section: Discussionmentioning
confidence: 99%
“…9 With a subcutaneously implanted amperometric glucose sensor, Matthews et al observed no lag in healthy subjects during a glucose clamp experiment. 10 In another study with a subcutaneously implanted biosensor, lag times ranging between 0 and 45 min were reported for peak glucose after a glucose load in healthy subjects. 11 In the same article, lag times of 0-15 min were reported for the glucose nadir in an insulin infusion test of healthy subjects.…”
Section: Introduction T Here Has Been a Great Deal Of Interest Inmentioning
confidence: 96%
“…Notably, needle-type, subcutaneous sensors containing GOD have been developed. In some cases, mediated sensors have also been proposed (Matthews et al 1988, Boutelle et al 1986Sakakida et al 1993, Linke et al 1994, despite the fact that it is difficult to retain low-molecular weight mediators at the electrode (Schuhmann et al 1990) and in face of evidence that xenobiotic mediators such as ferrocenes can have toxic effects (Leung et al 1987, Nikula et al 1993. Evaluation of the mutagenic activity of redox mediators seems to be necessary for at least two reasons: (1) safety of investigators constructing new biosensors and (2) preventing patients from possible prolonged exposure in the case of in vivo sensors.…”
Section: Introductionmentioning
confidence: 99%